Occlusal Contact Prints; A Biometric Means for Identification - Philip L. Millstein; Carlos E. Sabrosa (Journal of Advanced Forensic Sciences, 2022)
Fingerprints are commonly used for identification 1. All records are computerized. In a catastrophe recorded images of soft tissue may become useless if the tissues burn throughout. Dental prints are rarely used for identification. Information is taken from dental radiographs or dental casts. In case of fire recorded images of dental structures may be useful because they do not readily burn.
Keywords: Occlusion